Optimization of cyber security through the implementation of AI technologies - Nawaf Liqaa; Bentotahewa Vibhushinie (Journal of Intelligent Systems)
Identification of cyber threats is crucial and significant for determining substantial security techniques and approaches. This research illustrates a brief discussion of cyberspace challenges and threats in a disruptive era alongside comprehensive approaches in mitigating the risk of cyber threats. Additionally, the aim of this research is to provide beneficial approaches on how to handle cyber threats in detail. For example, threats and attacks may be caused in the absence of legislation, ethical standardization, support system, and lack of access control. The governance system, therefore, will put a lot of effort into communicating, identifying, and enforcing the principles of security to moderate risk. The Metaheuristic algorithms are stimulated by the human brain, so implementing Artificial Intelligence (AI) that assists the Neural Network to mimic the behaviour of the human brain is important to predict significant outcomes. In this study, the author investigates and analyses the rapid growth of cyber threats to outline the solutions. The aim of this study is to contribute to cyber security optimization through implementing AI methodologies.